Mortality and years of life lost of lung cancer among residents in Pudong New Area of Shanghai from 1995 to 2021 - ZHOU Yi; SHENG Jiayi; CHEN Yichen; LI Rongyue; XIAO Shaotan; PAN Jie (Shanghai yufang yixue, 2023)
ObjectiveTo investigate the epidemiological traits and potential years of life lost associated with lung cancer mortality among inhabitants of Shanghai's Pudong New Area from 1995 to 2021， in order to serve as a reference for developing intervention approaches.MethodsThe death surveillance system was used to gather statistics on lung cancer deaths. Crude mortality rate （CMR）， standardized mortality rate （SMR）， potential years of life lost （PYLL）， average years of life lost （AYLL）， annual percent change （APC） of the lung cancer deaths were analyzed. The impact of age-structural and non-age-structural factors on changes in lung cancer mortality was quantified using difference decomposition.ResultsThe CMR and SMR of lung cancer among residents in Pudong New Area between 1995 and 2021 were 58.21/105 and 26.75/105， respectively. The CMR of lung cancer increased over the years （APC=1.91%， 95%CI=1.60%‒2.30%； Z=11.487， P<0.001）， and the SMR of lung cancer declined over the years （APC=-1.50%， 95%CI=-1.80%‒-1.20%； Z=-9.006， P<0.001）. Age structure factors and gender factors contributed to the increase of lung cancer mortality， while non-population age structure factors overall appeared to play a protective role which might be related to the improvements in factors such as tobacco control and environmental management. The PYLL of lung cancer was 160 296 person years， the PYLL rate was 2.24‰， and the AYLL was 3.86 years per person.ConclusionAge structure factors are a significant contributor to the disease burden and result in the increase in the crude lung cancer mortality rate of Pudong residents of shanghai. Comprehensive monitoring， preventive， and control methods should be implemented.